Pharmacology of central synapses - Zakusov, Vasilii Vasilevich, 1903- (Pergamon Press, 1980)
Pharmacology of Central Synapses deals with the pharmacology of the central nervous system and the mode of action of neurotropic drugs based on their influence on synaptic transmission. The neuronal structure of the nervous system, the structure of the synapses, and the phenomena of electrochemical transmission are discussed in this context. The main propositions of the synaptic theory of the action of neurotropic drugs, based on morphological, physiological, and biochemical findings, form the conceptual basis of this book. Comprised of eight chapters, this book examines the effect of neurotro.